Feeding L-carnitine to gestating sows alters the insulin-like growth-factor system in cultured porcine embryonic muscle cells isolated from fetal skeletal muscle - A T Waylan; B J Johnson; D P Gnad; J C Woodworth (Kansas Agricultural Experiment Station Research Reports, 2004)
The objective was to determine the effects of L-carnitine on cell proliferation and on messenger RNA (mRNA) concentrations in the insulin-like growth factor (IGF) system. Cultured porcine embryonic myoblasts (PEM) were isolated from fetuses at mid-gestation from sows fed a common gestation diet with a 50-g top dress of 0 (control, n = 6) or 100 mg of L-carnitine (n = 6). Proliferation of PEM was evaluated at 36, 48, 60, and 72 h postplating. Real-time quantitative PCR was used to determine growth factor mRNA concentrations in culture. The number of cells/cm2 did not differ (P>0.05) from sows fed either diet, but the number of cells/cm2 increased (P<0.05) between each time period. There was a treatment × time interaction (P = 0.05) for number of doublings. The number of doublings was greater (P<0.01) between 36 and 48 h for PEM isolated from dams fed Lcarnitine, compared with that of the controls. When PEM were incubated with L-carnitine (n = 4) at six concentrations (3.125, 6.25, 12.5, 25, 50 and 100 Î¼mol/L) and compared with a control, no proliferation differences were detected (P>0.05). There was no treatment difference (P>0.05) for the expression of IGF-I or insulin-like growth factor binding protein 5 (IGFBP-5). But PEM isolated from sows fed L-carnitine had decreased (P<0.05) IGF-II, IGFBP-3, and myogenin (61, 59, and 67%, respectively) mRNA concentrations compared with those of controls. These data suggest that L-carnitine influences the IGF system and myogenin, resulting in enhanced proliferation and delayed differentiation of porcine embryonic myoblasts. These results show that L-carnitine plays a role in regulating proliferation and differentiation of cultured orcine embryonic myogenic cells and that etal muscle growth and development could be ncreased by feeding L-carnitine.; Swine Day, 2004, Kansas State University, Manhattan, KS, 2004
Keywords: Swine day; 2004; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 940; Kansas Agricultural Experiment Station contribution; no. 05-113-S; Insulin-like growth factor; Insulin-like growth factor binding protein; L-carnitine; Myoblasts; Pigs; Swine